Answer:
N=-6
Explanation:
Rearrange:
Rearrange the equation by subtracting what is to the right of the equal sign from both sides of the equation :
2*n-5-(9*n+37)=0
Step by step solution :
STEP 1 :
Pulling out like terms
1.1 Pull out like factors :
-7n - 42 = -7 • (n + 6)
Equation at the end of step :
STEP 2 :
Equations which are never true:
2.1 Solve : -7 = 0
This equation has no solution.
A a non-zero constant never equals zero.
Solving a Single Variable Equation:
2.2 Solve : n+6 = 0
Subtract 6 from both sides of the equation :
n = -6
Hope this helps!
Brain-List?